Modal Expressions, Adjectives, Adverbs and Nouns as Means for Expressing Root Modality in English and Their Translation Equivalents in Serbian - Mihić Pijetlović, Tijana R. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The paper analyses modal expressions, adjectives, adverbs and nouns expressing root modality in the English language. First, their modal meanings are defined and then their translation equivalents in the Serbian language are analyzed. The aim of the paper is to establish the translation equivalents of the analyzed words and expressions, the frequency of their occurrence as well as the level of equivalence. The obtained results show that modal nouns, adjectives and adverbs in English are most frequently translated by their equivalent modal nouns, adjectives and adverbs in Serbian. Modal verbs occur frequently in translation and we find them as translation equivalents of modal expressions, adjectives and nouns. As for the analyzed modal expressions, it is interesting to observe that some of them (be able / unable to, be to and be willing / unwilling to) are most frequently translated by modal verbs, while their corresponding modal expressions in Serbian occur less frequently. This high frequency of occurrence of modal verbs in translation can be explained by a wide range of meanings that they express (possibility, ability, permission, obligation, necessity, intention, volition, etc.). When translating modal concepts, translators must be particularly careful as expression of modal meanings can differ significantly among languages. Both English and Serbian have very rich resources for expressing modal meanings and the translator has to decide which of the available resources serves the purpose best in a given context or situation. The theory of equivalence on the level of word or phrase is the most acceptable one when translating modal meanings. The lower the level of equivalence is, the higher is the modal correspondence between the source and the target language.